Discovery of a Robust P‐Type Ultrawide Bandgap Oxide Semiconductor: LiGa5O8 - Kaitian Zhang; Vijay Gopal Thirupakuzi Vangipuram; Hsien‐Lien Huang; Jinwoo Hwang; Hongping Zhao (Advanced Electronic Materials)
Abstract LiGa5O8, an ultrawide bandgap semiconductor, is discovered to exhibit p‐type conductivity at room temperature, making it the widest bandgap p‐type oxide semiconductor known to date. Utilizing a mist–chemical vapor deposition (M–CVD) technique, successful growth of p‐type LiGa5O8 thin films on c‐plane sapphire and GaN‐on‐sapphire substrates is achieved. Characterization through X‐ray diffraction and cross‐sectional scanning transmission electron microscopy (STEM) confirms the spinel cubic crystal structure of LiGa5O8. Comprehensive investigations into the effects of growth conditions on surface morphology, material composition, and p‐type charge carrier transport are conducted. As‐grown LiGa5O8 thin films exhibit a broad range of hole concentrations, ranging from 1015 cm−3 to 1018 cm−3, depending on growth conditions. Elemental compositions of Li, Ga, and O are extracted using X‐ray photoemission spectroscopy (XPS). Both Li‐poor and Li‐rich LiGa5O8 films demonstrate p‐type conductivity. Optical absorption measurements reveal the bandgap of LiGa5O8 films to be ≈5.36 eV. Additionally, temperature‐dependent Hall measurements of the p‐type LiGa5O8 thin films show robust p‐conductivity down to 150 K. Results from this study promise the advancement of future power electronics based on ultrawide bandgap Ga2O3 and related semiconductor material systems.